Effects of toothache on the educational and social status of children - Dogan, Mehmet S; Aras, Ahmet; Atas, Osman; Karaali, Abdullah E; Gunay, Ayse; Akbaba, Haluk M; Yavuz, Izzet (UI Scholars Hub, 2019)
Background: Untreated tooth cavities and the resulting toothaches have significant effects on children’s social and psychological development. The aim of this study was to evaluate the impact of toothache on children’s educational and social activities. Methods: For this retrospective study, we issued a 15-question survey to the parents of 515 children between ages of 5–16 years in Diyarbakır, Turkey. The chi-square test was used to test the strength of the relationship between two variables (p ≤ 0.05). Results: 318 (61.7%) parents reported having difficulty in feeding their children, 94 (18.3%) left a game due to toothache, 173 (33.6%) had school absences, 167 (32.4%) avoided laughing, and 439 (85.2%) parents felt that dental problems influenced their child’s success in school. Conclusions: Tooth pain has a negative impact on school and the social lives of children. Families need education about this issue, and health policies should be developed to address this problem.